Analysis of documentation quality for early warning score monitoring Inpatient: retrospective observational study - Christina, Tri Yahya; Arsyta Putri, Rosalia Dian; Safaruddin, Safaruddin; Sriwiyati, Lilik; Andika, I Putu Juni; Yulianti, Tunjung Sri; Khairunisa, Fatimatuzzahra (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: One of the vital signs monitoring systems currently being developed in medical-surgical wards is the Early Warning Score (EWS). However, its implementation still needs to be evaluated, given the frequent occurrence of code blues and even deaths in the ward due to delays in recognizing deteriorating patient conditions. Purpose: To determine and analyze the quality of documentation regarding the implementation of EWS monitoring in patient setting. Method: A retrospective survey of patient medical records, supported by an assessment tool. Medical records were collected based on inclusion criteria, namely medical records from both medical and surgical wards. Results: The completeness of the EWS form was still quite low at 44%, with monitoring frequency accuracy at 12%, and total score calculation accuracy at 3.8%. Several important parameters that were incomplete and needed improvement included blood sugar (65%), which was the component with the lowest achievement; level of consciousness (84%), blood pressure (89%), temperature (90%), total score (89%), and escalation scale (88%), which was still suboptimal. Conclusion: The significant gap between the implementation of EWS monitoring and the accuracy of its documentation indicates that nurses' consistent documentation of EWS monitoring needs to be improved. This condition increases the risk of clinical deterioration, delayed intervention, serious complications, and even death. Inaccurate documentation also hinders interprofessional communication and increases the potential for clinical errors. Keywords: Documentation; Early Warning Score; Medical-Surgical Room; Patient Deterioration; Vital Signs.